Skeletal Muscle Cell Oxidative Stress as a Possible Therapeutic Target in a Denervation-Induced Experimental Sarcopenic Model. Issue 8 (15th April 2019) - Kinoshita, Hideyuki; Orita, Sumihisa; Inage, Kazuhide; Yamauchi, Kazuyo; Abe, Koki; Inoue, Masahiro; Norimoto, Masaki; Umimura, Tomotaka; Eguchi, Yawara; Fujimoto, Kazuki; Shiga, Yasuhiro; Kanamoto, Hirohito; et al.
Abstract : Study Design: A basic study using a rodent model of sarcopenia. Objective: To elucidate the contribution of oxidative stress to muscle degeneration and the efficacy of antioxidant treatment for sarcopenia using an animal model of neurogenic sarcopenia. Summary of Background Data: Oxidative stress has been reported to be involved in a number of pathologies, including musculoskeletal disorders. Its relationship with sarcopenia, one of the potential origins of lower back pain, however, is not yet fully understood. Methods: Myoblast cell lines (C2C12) were treated with H2 O2, an oxidative stress inducer, and N -acetyl-L-cysteine (NAC), an antioxidant. Apoptotic effects induced by oxidative stress and the antioxidant effects of NAC were assessed by western blotting, immunocytochemistry, and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) cell viability assays. An animal model of sarcopenia was produced via axotomy of the sciatic nerves to induce muscle atrophy. Twenty-four male Sprague-Dawley rats were divided into sham, sham+NAC, axotomy, and axotomy+NAC groups. Rats were provided water only or water containing NAC (1 g/L) for 4 weeks. The gastrocnemius muscle was isolated and stained with hematoxylin and eosin (H&E) 2 weeks after axotomy, from which muscle cells were harvested and protein extracted for evaluation. Results: Mitogen-activated protein kinases (MAPKs) were significantly activated by H2 O2 treatment in C2C12 cells, which was ameliorated by NAC pretreatment. Furthermore, H2 O2 induced apoptosis and death of C2C12 cells, which was prevented by NAC pretreatment. The weight of the gastrocnemius muscle was reduced in the axotomy group, which was prevented by NAC administration. Lastly, although muscle specimens from the axotomy group showed greater reductions in muscle fiber, the oral administration of NAC significantly inhibited amyotrophy via antioxidant effects. Conclusion: The current in vitro and in vivo study demonstrated the possible involvement of oxidative stress in sarcopenic pathology. NAC represents a potential anti-sarcopenic drug candidate, preventing amyotrophy and fatty degeneration. Level of Evidence: 4 Abstract : In myoblasts, oxidative stress caused apoptosis via the MAPK pathway, which was prevented by NAC pretreatment. In a rodent model of sarcopenia, sciatic nerve axotomy induced oxidative stress in muscle, leading to amyotrophy and fatty degeneration, which were improved with NAC in vivo . NAC is a potential anti-sarcopenic drug candidate.